HEPATITIS B SURFACE EXAMINATION PICTURE ANTIGENS ON CLEANING OFFICERS WORKING AT DUNDA LIMBOTO Hospital - Eni Muliawati, Ni Nyoman; Dunggio, Titin (Journal of Health, Technology and Science (JHTS), 2023)
This study aims to determine the results of hepatitis B examination on janitors at RSUD Dr. MM Dunda Limboto. The method in this study used a qualitative descriptive, immunochromatography method, focused on examining hepatitis B and identifying risks to the safety and health of janitors working at Dunda Limboto Hospital, Gorontalo Regency.The results showed that the examination of hepatitis b surface antigen on hospital cleaners, with a total sample of 14 serum samples using the HBsAg rapid test tool, the results obtained were 100 non reactive. Non-reactive results were obtained from the HBsAg rapid test tool, which only appeared a red line in the Control (C) area, while in the Test (T) area there was no red line. research results all samples (100%) Non Reactive. Suggestions for cleaners to be further improved in maintaining health and paying attention to safety when working, especially wearing personal protective equipment (masks, safe clothes, gloves, safe shoes if needed)